2021
DOI: 10.3390/nano11051336
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Nanoparticles and Their Nanocomposites

Abstract: Lignin nanomaterials have emerged as a promising alternative to fossil-based chemicals and products for some potential added-value applications, which benefits from their structural diversity and biodegradability. This review elucidates a perspective in recent research on nanolignins and their nanocomposites. It summarizes the different nanolignin preparation methods, emphasizing anti-solvent precipitation, self-assembly and interfacial crosslinking. Also described are the preparation of various nanocomposites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 161 publications
(215 reference statements)
0
59
0
Order By: Relevance
“…The equilibrium removal rate of SA/LNPs-40 beads reaches to 97.1% compared to 82.9% and 77.4% of SA/L and SA, respectively. Such an increase could be ascribed to the presence of LNPs in the beads [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The equilibrium removal rate of SA/LNPs-40 beads reaches to 97.1% compared to 82.9% and 77.4% of SA/L and SA, respectively. Such an increase could be ascribed to the presence of LNPs in the beads [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such a process, indeed, aids to overcome the non-homogeneity of lignin. More importantly, the resulting nano-character coupled with amounts of functional groups, large specific surface area, high diffusibility and compatibility, and low-cost nature opens up novel opportunities for lignins [ 11 , 12 ]. For example, lignin nanoparticles (LNPs) are helpful to fabricate novel and well-performing bio-nanocomposite materials [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Gilca et al used ultrasonic irradiation to obtain LiG NPs from wheat straw and sarkanda grass [ 40 ]. Additionally, by using several characterization techniques, it has also been confirmed that ultrasonication at the intensity applied for breaking down bulk particles is not responsible for changes in either the structure or composition of the synthesized LiG NPs [ 66 , 67 , 68 ].…”
Section: Different Methods For Lig Nps Synthesismentioning
confidence: 99%
“…LNPs were prepared starting from Kraft Lignin (KL) by the nanoprecipitation technology [50] that requires the dissolution of the polymer in a primary solvent followed by addition of deionized water (secondary solvent) [51]. After the addition of water, lignin quickly aggregates in order to balance repulsive electrostatic forces, thus yielding stable colloidal nanoparticles that can entrap bioactive substances in their internal cavity [47,52].…”
Section: Lignin Nanoparticles As a Drug Delivery System For Biomimetic Thymine Dimers And Photo-adductsmentioning
confidence: 99%